2021
DOI: 10.3390/ijms221910600
|View full text |Cite
|
Sign up to set email alerts
|

Imatinib Regulates miR-483-3p and Mitochondrial Respiratory Complexes in Gastrointestinal Stromal Tumors

Abstract: Metabolic adaptation to increased oxidative phosphorylation (OXPHOS) has been found in gastrointestinal stromal tumor (GIST) upon imatinib treatment. However, the underlying mechanism of imatinib-induced OXPHOS is unknown. Discovering molecules that mediate imatinib-induced OXPHOS may lead to the development of therapeutic strategies synergizing the efficacy of imatinib. In this study, we explored the role of microRNAs in regulating OXPHOS in GIST upon imatinib treatment. Using a microarray approach, we found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…A recent study demonstrated that IM specifically increases the expression of the complex II (SDHB) protein in oxidative phosphorylation (OXPHOS) proteins by downregulating miR-483-3p (Figure 1A). This study demonstrated the molecular mechanism of increased OXPHOS protein expression induced by IM and confirmed the biological role of miR-483-3p in regulating energy metabolism after IM treatment (20).This review will focus on the discussion and summary of research on the mechanisms of secondary resistance to IM conducted in the last 5 years from the aspects of abnormal gene mutation, energy metabolism, non-coding RNA, and key proteins.…”
Section: Introductionsupporting
confidence: 55%
“…A recent study demonstrated that IM specifically increases the expression of the complex II (SDHB) protein in oxidative phosphorylation (OXPHOS) proteins by downregulating miR-483-3p (Figure 1A). This study demonstrated the molecular mechanism of increased OXPHOS protein expression induced by IM and confirmed the biological role of miR-483-3p in regulating energy metabolism after IM treatment (20).This review will focus on the discussion and summary of research on the mechanisms of secondary resistance to IM conducted in the last 5 years from the aspects of abnormal gene mutation, energy metabolism, non-coding RNA, and key proteins.…”
Section: Introductionsupporting
confidence: 55%
“…Moreover, the roles of microRNAs in regulating OXPHOS towards imatinib resistance of GISTs were recently explored. Huang et al found that miRNA-483-3p, whose expression was downregulated in imatinib-treated GIST samples, could inhibit the protein expression of mitochondrial respiratory Complex II, thus increasing the cell death induced by imatinib in GIST cells ( Huang et al, 2021 ). OXPHOS played a pivotal role in the drug resistance of GIST and the detailed mechanisms between cell metabolism and ncRNAs in the drug resistance need further investigation.…”
Section: Regulating Roles Of Noncoding Rna In Drug Resistance Of Gast...mentioning
confidence: 99%
“…Moreover, reducing influence of miRNA-218 on imatinib resistance was proved by Fan et al ( Fan et al, 2014 ; 2015 ). There were also other miRNAs, such as miRNA-483-3p ( Huang et al, 2021 ), miRNA-518e-5p ( Kou et al, 2018 ), miRNA-518a-5p ( Shi Y. et al, 2016 ), miRNA-148b-3p ( Wang Y. et al, 2018 ), miRNA-17-92 ( Gits et al, 2013 ), miRNA-21 ( Cao et al, 2016 ), miRNA-23b ( Cao J. et al, 2018 ), miRNA-30a ( Zheng et al, 2015 ), miRNA-320a ( Gao et al, 2014 ), miRNA-505 ( Cao J. et al, 2018 ), miRNA-92a-3p ( Amirnasr et al, 2019 ) and miRNA-99a-5p ( Amirnasr et al, 2019 ), being identified or demonstrated that they played important roles in the process of imatinib resistance in GISTs.…”
Section: Different Types Of Noncodingrnas On the Drug Resistance Of G...mentioning
confidence: 99%
See 2 more Smart Citations